Reframing Women: Gender and Film in Aotearoa New Zealand 1999–2014. (February 2015) - Shepard, Deborah
When my book Reframing Women: A history of New Zealand cinema (Harper Collins) was published in 2000 New Zealand women's film was flourishing. There had been an explosion of filmmaking following the upsurge of twentieth century feminism in the 1970s beginning with the international women's year film Some of My Best Friends are Women (1975) and the subsequent production of nine feminist documentary films. The energy generated by these films and the international feminist history projects that uncovered the formerly invisible contribution of women across every sphere of creative was contagious. There was a feeling of optimism that anything was possible. Women were using the camera to focus the lens on themselves and their issues. Between 1980 and 1990 dramas and features dealing with gender issues increased dramatically while the formerly marginalised were gaining access to the technology to explore sexuality and identity politics. There were powerful films about identity by Maori, Pacific, Asian, Yugoslavian, Greek … and increasing experimentation with film form. Since 2000 women have lost ground and film production and experimentation has declined, knocked back by the backlash against feminism, by recession and fiscal cutbacks caused by the global financial meltdown of 2008–9 and a change in political parties to a conservative, misogynist, right wing, capitalist government. I propose to investigate the situation and the changes in the film climate with reference to the global situation through a series of interviews with key creatives: leading feminist film director Gaylene Preston, academic documentary film director Annie Goldson, feature film directors Christine Jeffs ( Rain and Sylvia about Sylvia Plath) and Fiona Samuel ( Bliss about the life of Katherine Mansfield), the Greek feminist academic film director Athina Tsoulis, Maori screenwriter Riwia Brown ( Once Were Warriors ), Samoan director Justine Simei-Barton, Indian academic Schuchi Kotari and the cinematographer Mairi Gunn, along with a younger feminist director Brita McVeigh. The paper will compare my historical findings in reframing women with the current situation in a blend of history, current opinion and analysis and reflection.